Identity motives and passion: The mediating role of identifying with an activity - Krzysztof Kwapis; Anna M. Batory-Ginda (Multidisciplinary Journal of School Education)
Research objectives and problems: Favorite activities often become central to self-definition, as passions and identity intertwine. This study examined whether the satisfaction of six identity motives—distinctiveness, continuity, self-esteem, belonging, efficacy, and meaning—predicts the strength and type of passion, and whether identifying with an activity mediates these relationships.